Human Zona Pellucida Glycoproteins: Binding Characteristics With Human Spermatozoa and Induction of Acrosome Reaction - Gupta, Satish Kumar (Frontiers in Cell and Developmental Biology, 2021)
Human zona pellucida (ZP) matrix is composed of four glycoproteins designated as ZP glycoprotein -1 (ZP1), -2 (ZP2), -3 (ZP3), and -4 (ZP4). Mutations in the genes encoding human ZP glycoproteins are one of the causative factors leading to abnormal ZP matrix and infertility in women. Relevance of the human ZP glycoproteins in ‘sperm-oocyte’ binding has been delineated by using either transgenic animal models expressing human zona proteins or purified native/recombinant human zona proteins. Studies based on the purified native/recombinant human zona proteins revealed that ZP1, ZP3, and ZP4 primarily bind to the capacitated acrosome-intact human spermatozoa whereas ZP2 binds to acrosome-reacted spermatozoa. On the contrary, human spermatozoa binds to the eggs obtained from gene-edited mouse lines expressing human ZP2 but not to those expressing human ZP1, ZP3, and ZP4 suggesting that ZP2 has an important role in human ‘sperm-oocyte’ binding. Further studies using transgenic mouse lines showed that the N-terminus of human ZP2 mediate the taxon-specific human sperm-oocyte binding. Both glycans and protein-protein interactions have a role in human gamete interaction. Further studies have revealed that the purified native/recombinant human ZP1, ZP3, and ZP4 are competent to induce acrosome reaction. In human ZP2Rescue mice, human sperm bind to the egg, penetrated the ZP matrix and accumulated in the perivitelline space, which were acrosome-reacted suggesting that human ZP2 in transgenic mouse model also induce acrosome reaction. In humans N-linked glycosylation of zona proteins have been shown to play an important role in induction of the acrosome reaction. Hence in humans, based on studies using transgenic mouse model as well as purified native/recombinant zona proteins, it is likely that more than one zona protein is involved in the ‘sperm-oocyte’ binding and induction of the acrosome reaction.